Approach to the clinical care of dysphagia in a population with a neurological diagnosis at an institution in Cúcuta, Norte de Santander (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2019)
INTRODUCTION: The research sought to describe the clinical approach to dysphagia in the oropharyn-geal phases of swallowing through objective and subjective evaluation procedures. METHODS: This is a descriptive quantitative cross-sectional study accompanied by a field work with 10 users carried out through the MBGR orofacial Myofunctional Exam, Clinical Evaluation of Dysphagia and Complemen-tary Methods. RESULTS: A structural and functional organization of the stomatognathic system was carried out, showing the variables that each user provided in support of graphs, tables. ANALYSIS AND DISCUSSION: the clinical evaluation of dysphagia includes a series of complementary techniques of subjective and objective nature that provides a greater approximation and precision when determin-ing a diagnosis of swallowing disorders CONCLUSIONS: The use of all complementary methods for the clinical evaluation of dysphagia is essential
Keywords: Swallowing; Dysphagia; Anthropometric measurements; evaluation method; Myofunctional